2022
DOI: 10.3390/cancers14112739
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Radiomics and Deep Learning for BRCA Mutation and Progression-Free Survival Prediction in Ovarian Cancer Using a Multicentric Dataset

Abstract: Purpose: Build predictive radiomic models for early relapse and BRCA mutation based on a multicentric database of high-grade serous ovarian cancer (HGSOC) and validate them in a test set coming from different institutions. Methods: Preoperative CTs of patients with HGSOC treated at four referral centers were retrospectively acquired and manually segmented. Hand-crafted features and deep radiomics features were extracted respectively by dedicated software (MODDICOM) and a dedicated convolutional neural network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The results demonstrated that combining clinical and radiomics models improved model performance. This finding was consistent with the research of Avesani [ 39 ], who built predictive radiomics models for early relapse and BRCA mutation based on a multicentric database of OC. Their models showed low performance in predicting both BRCA mutation and 1-year relapse with traditional radiomics (AUC: 0.46-0.59 for BRCA and 0.46-0.56 for relapse) and deep learning (AUC of 0.48 BRCA and 0.50 for relapse).…”
Section: Discussionsupporting
confidence: 91%
“…The results demonstrated that combining clinical and radiomics models improved model performance. This finding was consistent with the research of Avesani [ 39 ], who built predictive radiomics models for early relapse and BRCA mutation based on a multicentric database of OC. Their models showed low performance in predicting both BRCA mutation and 1-year relapse with traditional radiomics (AUC: 0.46-0.59 for BRCA and 0.46-0.56 for relapse) and deep learning (AUC of 0.48 BRCA and 0.50 for relapse).…”
Section: Discussionsupporting
confidence: 91%
“…Despite not distinguishing between subtypes, the radiomics model developed by Liu et al achieved an AUC of 0.82 in predicting BRCA gene mutation status in EOC (16). Another multicenter study applied radiomics models that included first order statistical features, shape features, and textural features based on machine-learning algorithms to assess the BRCA mutation status of HGSOC, but the models did not include filter features and all of them presented a low performance (21). However, the subsequently added clinical indicator (CA125 level) brought improvements to the performance of the models in assessing BRCA mutation (AUC = 0.74).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies so far investigated the correlation of radiomics feature and gene expression profile in various malignancies with a main focus on Non-Small Cell Lung Cancer (NSCLC) [ 43 , 44 , 45 ]. For example, Zhang et al [ 44 ] constructed a clinical-radiological-radiomics model (C-R-R), based on the combination of CT radiomics feature signature with clinical and radiological features, aiming to predict epidermal growth factor receptor (EGFR) status among 420 patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%